A Western And Eastern Learning Model For Teaching â€œYoung Artistsâ€ Painting Style In Indonesia - Lodra, I Wayan; Arif, Muchlis (Institut Seni Indonesia Denpasar, 2020)
Every country in the world has its own learning models, which depend on the social, cultural, and economic conditions of the nation. In principle, learning aims to transfer knowledge, technology, and information to others to free them from ignorance. In developing countries like Indonesia, learning models vary in every educational institution. Educational institutions can be categorized according to the characteristics of the learner, and include formal, informal, and non-formal education. It is not possible to apply the same learning models to educational institutions with different geographical, social, and cultural conditions. Bali is an Indonesian province which has developed formal, informal, and non-formal education in the field of painting. One outcome of this non-formal education is the â€œYoung Artistsâ€ style. This non-formal learning model, developed by Arie Smit, combines western and eastern learning models. The research focuses on how Arie Smitâ€™s eastern and western learning model was applied to children from the village of Penestanan, Ubud, Bali. The goal is to describe Arie Smitâ€™s western and eastern learning model that he used with children from Panestanan Ubud, Bali. The research method is qualitative descriptive and the data collection techniques include observation, interviews, and documentation. The analysis was performed by studying, disentangling, arranging, and summarizing the â€œYoung Artistsâ€ learning model for teaching painting. The research findings show that this western and eastern learning model applies a method of cooperative active teaching.